Special features of the artistic conceptualisation of eros love in the poetry of the representatives of the Executed Renaissance - Літвінова, Інна Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article studies the image system of the poetry of the Executed Renaissance, which is a special artistic phenomenon in Ukrainian and world literature. Among the outstanding representatives of the period are B.-I. Antonych, M. Bazhan, M. Yohansen, H. Koliada, B. Lepkyi, V. Pluzhnyk, M. Rylskyi, M. Semenko, V. Sosiura, P. Tychyna and others.The research analyses erotic images and motifs – the ones realised on the border of the spiritual and the corporeal. The choice of the research data is determined by the esthetics of the analysed period: the authors of the 1920-1930s loved freedom and were free in expressing themselves, they believed there could not be taboos in literature. The analised images are realized in various theme dimensions: sexual relationship, social relationship, intellectual activity, art etc. Because of their specific character they have become a kind of ways of guiding any topic into the area of the most intimate experiences and, as such, the markers of the significance of the depicted. Using different literary techniques, the authors create original images that exist within several discourses, so multidimensionality and various semantic transformations can be pointed out as the specific features of the analysed images. The sensuality of the erotic images created within modernistic esthetics is sometimes intensified by the rhythmomelodics or experiments at the sound or lexical levels.It is pointed out that research of the erotic images in the texts of the representatives of Executed Renaissance is important as in case of ignoring the erotic in literature, we go on living within Soviet discourse. Besides, the actualisation of such imagery has intensified the sensuality and the depth of the text, thus taking Ukrainian literature and language to a new level. Because of the artificial interruption in the natural course of the literary process in Ukraine in the first part of the 20th century, a kind of repetition of the trend can be observed at modern stage. Considering the above, the suggested angle of research on poetry looks still more topical and perspective.